Hadith Scholarship Over Two Decades, 2000–2025: A Bibliometric Portrait of Trends and Influential Works - Judijanto, Loso (West Science Islamic Studies, 2026)
This research attempts to shed light on the development of Hadith science between 2000 and 2025 through a bibliometric examination of its intellectual structure, collaboration patterns, and thematic changes. The analysis of the literature, which was extracted from the Scopus database with the help of VOSviewer, is focused on three major dimensions – namely, co-authorship, citations, and keywords co-occurrences. As shown by the obtained results, Hadith science continues to preserve its strong ties to classical Islamic scholarship, represented primarily by theology, Shariah, and the history of Islam in its early days. However, Hadith science has expanded significantly beyond its traditional boundaries, having entered new disciplines such as multicultural education, gender-related issues, and even modern society's problems. Regarding co-authorships, it becomes evident that Hadith science possesses an internally coherent network of collaboration that, however, tends to be quite region-specific. Finally, when it comes to keywords co-occurrences, one can notice that the most popular topics among those covered in this field include Hadith's digital discourse and epistemology. To sum up, this study suggests that Hadith scholarship is currently going through a transition process, when classical traditions continue to be followed alongside more innovative ones.